Synergistic co-metabolism enhancing the crude oil degradation by Acinetobacter oleivorans DR1 and its metabolic potential - Lairenjam Paikhomba Singha; Renuka Kumari; Keisam Malabika Singha; Piyush Pandey; Pratyoosh Shukla (Microbiology Spectrum)
ABSTRACT Bacterial degradation of hydrocarbons during co-metabolism with glucose often resulted in variable degradation efficiency. This study explored the mechanistic understanding of the metabolic response during co-metabolism in Acinetobacter oleivorans DR1 using a metabolomics approach. We reported that glucose slowed the growth rate of DR1 with a 7-h lag phase in a combined media containing crude oil, glucose, and biosurfactant, yet glucose supplement enhanced the degradation rates by 31% for dodecane and 18% for triacontane compared to culture amended with crude oil and biosurfactant. This demonstrated that glucose may not be the preferred carbon and energy source, but it still significantly influences hydrocarbon metabolism through increased synthesis of fatty acids and low molecular weight organic acids (glutaric, citric, and tartaric acid, etc.). Principal component analysis revealed the distinct clusters of metabolites among the culture conditions, highlighting the minimal effect of biosurfactant. Our study reports the role of significant metabolites in crude oil culture, proving the gluconeogenesis capability of DR1. The pre-screening of the metabolic pathway concluded that trehalose was crucial in combating stress imposed during hydrocarbon degradation. Hence, A. oleivorans DR1 can be used to degrade hydrocarbons and has a pivotal role in synergistic co-metabolism during crude oil degradation.IMPORTANCEIn hydrocarbon-contaminated soil, the presence of easily metabolizable carbon sources can lead to carbon catabolite repression. This repression reduces the activity of hydrocarbon-degrading bacteria, slowing down the rate of bioremediation. In this study, the most robust yet underexplored tool—liquid chromatography-high resolution accurate mass spectrometry system—was used to study the metabolic response and functional state of A. oleivorans DR1 during the crude oil degradation in the presence or absence of either biosurfactant or glucose supplementation. Here, synergistic co-metabolism by DR1 for crude oil degradation is reported. DR1 preferred hydrocarbons over glucose since glucose was not readily utilizable due to lack of enzymes (e.g., glucokinase). However, the glucose enhanced the hydrocarbon degradation in DR1 through the high production of organic acids that reacted on hydrocarbon chains and underwent fatty acid synthesis. This study added Acinetobacter oleivorans DR1's strength towards hydrocarbon utilization and proposed it as an effective agent for bioremediation.